2018
DOI: 10.1007/s00449-018-1923-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen uptake rate as a tool for on-line estimation of cell biomass and bed temperature in a novel solid-state fermentation bioreactor

Abstract: Direct measurement of cell biomass is difficult in a solid-state fermentation (SSF) process involving filamentous fungi since the mycelium and the solid substrate are often inseparable. However, respiratory data are rich in information for real-time monitoring of microbial biomass production. In this regard, a correlation was obtained between oxygen uptake rate (OUR) and biomass concentration (X) of Rhizopus oryzae MTCC 1987, during phytase production, in an intermittently mixed novel SSF bioreactor. To obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The regression analysis of the fungal biomass production and the content of oxygen consumption shown in Table 1C revealed that the amount of oxygen consumed, fermentation time, and their interaction all had significant impact on fungal growth. Contrary to the findings of Arora et al (2018) who found that the oxygen consumption rate was directly related to Rhizopus oryzae cell biomass production, the present work showed the impact of the growth phase and the amount of oxygen supply on the growth since they affected the content of oxygen consumption. This was supported by the work of Bastos et al (2016) in which increased biomass and protein production using polyurethane foam as an inert support to increase oxygen transfer, since oxygen uptake affected enzyme production, which was required for fungal growth (Zhou et al, 2018;Abdella et al, 2020).…”
Section: Red Pigment Productioncontrasting
confidence: 99%
“…The regression analysis of the fungal biomass production and the content of oxygen consumption shown in Table 1C revealed that the amount of oxygen consumed, fermentation time, and their interaction all had significant impact on fungal growth. Contrary to the findings of Arora et al (2018) who found that the oxygen consumption rate was directly related to Rhizopus oryzae cell biomass production, the present work showed the impact of the growth phase and the amount of oxygen supply on the growth since they affected the content of oxygen consumption. This was supported by the work of Bastos et al (2016) in which increased biomass and protein production using polyurethane foam as an inert support to increase oxygen transfer, since oxygen uptake affected enzyme production, which was required for fungal growth (Zhou et al, 2018;Abdella et al, 2020).…”
Section: Red Pigment Productioncontrasting
confidence: 99%
“…Ikasari and Mitchell (1998), using the Rhizopus oligosporus SSF process with rice bran as the substrate, observed similar results and reported an increase in OUR and heat evolved around 24 h, as well as a significance decrease was reported at 72 h fermentation. This finding was supported by Arora et al (2018), where a correlation was obtained between OUR and biomass concentration of R. oligosporus MTCC 1987 during phytase production in an intermittently mixed novel SSF bioreactor.…”
Section: Our and Cer As A Tool For Online Monitoring Of Fungal Growthsupporting
confidence: 56%
“…The current trend in modern bioprocess technology is to monitor the process itself, not only by measuring the usual variables (concentrations in the bioreactor, pH, temperature, and the concentrations of the components of the off-gas and its flow) [41][42][43][44][45], but also by following the metabolic states of the cells [46]. FCM is usually used to count bacteria of different types and states, and to characterize bacterial physiology under different environmental conditions [47].…”
Section: Discussionmentioning
confidence: 99%